The rise of populist radical right parties in Europe - Aktas, Murat (Sage Publications Ltd, 2024)
After World War II, radical right parties in Europe experienced a decline, but over the last three decades, they have regained strength, becoming significant players in European politics. Since the early twenty-first century, they have secured representation at various levels, from local governments to national parliaments and the European Parliament. Nowadays, populist radical right parties rank among the top three most powerful political forces in one-third of European countries. In Austria, the FPO (Freiheitliche Partei Osterreichs) emerged as the leading party in the 2024 elections, winning 28.9% of the vote. In Italy, the Fratelli d'Italia coalition came to power with 25.99% of the vote in 2022. In Hungary, Viktor Orban's Fidesz party won its fourth consecutive election. In France, Marine Le Pen's National Rally (RN - Rassemblement National) achieved major victories in both the European Parliament and national elections, becoming the country's largest party. Though initially considered marginal, populist radical right parties have become a lasting and serious force in European politics. This special issue features six carefully selected articles, each offering empirical and theoretical insights into different aspects of the rise of radical right and right-wing populist parties in Europe, contributing to a broader understanding of this phenomenon.
Keywords: Far-right; nativist; populism; populist radical right; radical right; anti-immigrant